Specific alterations in complement protein activity of little brown myotis (Myotis lucifugus) hibernating in white-nose syndrome affected sites. - Marianne S Moore; Jonathan D Reichard; Timothy D Murtha; Bita Zahedi; Renee M Fallier; Thomas H Kunz (PLoS ONE, 2011)
White-nose syndrome (WNS) is the most devastating condition ever reported for hibernating bats, causing widespread mortality in the northeastern United States. The syndrome is characterized by cutaneous lesions caused by a recently identified psychrophilic and keratinophylic fungus (Geomyces destructans), depleted fat reserves, atypical behavior, and damage to wings; however, the proximate cause of mortality is still uncertain. To assess relative levels of immunocompetence in bats hibernating in WNS-affected sites compared with levels in unaffected bats, we describe blood plasma complement protein activity in hibernating little brown myotis (Myotis lucifugus) based on microbicidal competence assays using Escherichia coli, Staphylococcus aureus and Candida albicans. Blood plasma from bats collected during mid-hibernation at WNS-affected sites had higher bactericidal ability against E. coli and S. aureus, but lower fungicidal ability against C. albicans when compared with blood plasma from bats collected at unaffected sites. Within affected sites during mid-hibernation, we observed no difference in microbicidal ability between bats displaying obvious fungal infections compared to those without. Bactericidal ability against E. coli decreased significantly as hibernation progressed in bats collected from an affected site. Bactericidal ability against E. coli and fungicidal ability against C. albicans were positively correlated with body mass index (BMI) during late hibernation. We also compared complement activity against the three microbes within individuals and found that the ability of blood plasma from hibernating M. lucifugus to lyse microbial cells differed as follows: E. coli>S. aureus>C. albicans. Overall, bats affected by WNS experience both relatively elevated and reduced innate immune responses depending on the microbe tested, although the cause of observed immunological changes remains unknown. Additionally, considerable trade-offs may exist between energy conservation and immunological responses. Relationships between immune activity and torpor, including associated energy expenditure, are likely critical components in the development of WNS.